Le vere sfide delle città intelligenti - Murgante, Beniamino; Borruso, Giuseppe (GEOmedia, 2014)
A recent study by the Economist shows that despite the United States and European Union they have comparable population, in U.S. population of 164 million people reside in the top 50 metropolitan areas where Europe stops at 102 million. This gap leads to surprising consequences in terms of productivity and income.